2016
DOI: 10.1371/journal.pgen.1006307
|View full text |Cite|
|
Sign up to set email alerts
|

Altered mRNA Splicing, Chondrocyte Gene Expression and Abnormal Skeletal Development due to SF3B4 Mutations in Rodriguez Acrofacial Dysostosis

Abstract: The acrofacial dysostoses (AFD) are a genetically heterogeneous group of inherited disorders with craniofacial and limb abnormalities. Rodriguez syndrome is a severe, usually perinatal lethal AFD, characterized by severe retrognathia, oligodactyly and lower limb abnormalities. Rodriguez syndrome has been proposed to be a severe form of Nager syndrome, a non-lethal AFD that results from mutations in SF3B4, a component of the U2 small nuclear ribonucleoprotein particle (U2 snRNP). Furthermore, a case with a phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 77 publications
(79 reference statements)
6
26
1
Order By: Relevance
“…One of the possibilities that cause this morphological change is that down‐regulation of Sf3b4 expression affects Sf3b1 expression level. However, the SF3B1 expression level is not significantly different in a patient of Rodriguez syndrome (heterozygous mutation of SF3B4 ) compared to control . Importantly, Isono et al have shown that SF3b4 forms a complex with Rnf2 and Zfp144 as Sf3b1 does.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…One of the possibilities that cause this morphological change is that down‐regulation of Sf3b4 expression affects Sf3b1 expression level. However, the SF3B1 expression level is not significantly different in a patient of Rodriguez syndrome (heterozygous mutation of SF3B4 ) compared to control . Importantly, Isono et al have shown that SF3b4 forms a complex with Rnf2 and Zfp144 as Sf3b1 does.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study using specimens of Rodriguez syndrome patients with haploinsufficiency of SF3B4 showed that mRNA splicing is altered in fetal chondrocytes . In contrast, an in vitro study reported that human SF3b4 regulates osteochondral differentiation by interacting with bone morphogenetic protein (BMP) receptor, BMPR‐I .…”
Section: Introductionmentioning
confidence: 99%
“…Devotta et al () found that some genes involved in NCC development were down‐regulated, however, they did not find evidence to support the hypothesis that the down‐regulation of these genes was associated with defective splicing. In contrast, a recent study by Marques et al () in human tissue showed that mRNA splicing is impaired in chondrocytes of fetuses with Rodriguez syndrome, which is a more severe and lethal form of Nager syndrome that is also caused by mutations in SF3B4 . SF3B4 has also been reported to bind to BMPR‐IA and inhibit BMP‐mediated osteochondral cell differentiation, which may also contribute to skeletal defects (Nishanian and Waldman, ; Watanabe, Shionyu, Kimura, Kimata, & Watanabe, ).…”
Section: Developmental Processes Linking Spliceosomopathies and Ribosmentioning
confidence: 86%
“…Among these selected RNA binding proteins, we included factors that are core splicing factors but which also have been shown to alter alternative splicing. These include U2AF1, U2AF2, SF3A3, and SF3B4 [53][54][55][56][57]. Out of these 27 unique eCLIP assayed factors, 16 splicing regulators were also studied in both cell lines.…”
Section: Extensive Rust Revealed By a Splicing Factor Interaction Netmentioning
confidence: 99%